Between state and synagogue : the secularization of Contemporary Israel - Ben-Porat, Guy. (Cambridge : Cambridge University Press, 2013)
'A thriving, yet small, liberal component in Israeli society has frequently taken issue with the constraints imposed by religious orthodoxy, largely with limited success. However, as this thoughtful new book by Guy Ben-Porat suggests, in recent years, in part because of demographic changes and in part because of the influence of an increasingly consumer-oriented society, dramatic changes have occurred in secularization of significant parts of public and private lives. Even though these fissures often have more to do with lifestyle choices and economics than with political or religious ideology, the demands and choices of a secular public and a burgeoning religious presence in the government are becoming ever more difficult to reconcile. The evidence, which the author has accrued from numerous interviews and a detailed survey, is nowhere more telling than in areas that demand religious sanction such as marriage, burial, the sale of pork, and the operation of businesses on the Sabbath. This book makes an important and timely contribution to the study of contemporary Israeli society, as new alliances are being forged in the political arena'--
Unpacking secularization -- Israel: from status quo to crisis -- The state of marriage: regulating and de-regulating love -- Burial: a matter of lifestyle -- Pig on the plate: from'white steak' to pork -- Live and let buy: bargaining for the Sabbath.
Includes bibliographical references (p. 229-245) and index.
Keywords: Judaism -- Israel; Judaism and state -- Israel; Secularism -- Israel; Jews -- Israel -- Identity; Israel -- Politics and government